Biomaterial-Supported Cell Transplantation Treatments for Spinal Cord Injury: Challenges and Perspectives - Liu, Shengwen; Schackel, Thomas; Weidner, Norbert; Puttagunta, Radhika (Frontiers in Cellular Neuroscience, 2018)
Spinal cord injury (SCI), resulting in para- and tetraplegia caused by the partial or complete disruption of descending motor and ascending sensory neurons, represents a complex neurological condition that remains incurable. Following SCI, numerous obstacles comprising of the loss of neural tissue (neurons, astrocytes and oligodendrocytes), formation of a cavity, inflammation, loss of neuronal circuitry and function must be overcome. Given the multifaceted primary and secondary injury events that occur with SCI treatment options are likely to require combinatorial therapies. While several methods have been explored, only the intersection of two, cell transplantation and biomaterial implantation, will be addressed in detail here. Owing to the constant advance of cell culture technologies, cell-based transplantation has come to the forefront of SCI treatment in order to replace/protect damaged tissue and provide physical as well as trophic support for axonal regrowth. Biomaterial scaffolds provide cells with a protected environment from the surrounding lesion, in addition to bridging extensive damage and providing physical and directional support for axonal regrowth. Moreover, in this combinatorial approach cell transplantation improves scaffold integration and therefore regenerative growth potential. Here, we review the advances in combinatorial therapies of Schwann cells, astrocytes, glial-restricted progenitors, glial-restricted progenitor-derived astrocytes, olfactory ensheathing cells, mesenchymal stem cells, as well as neural stem and progenitor cells with various biomaterial scaffolds.